Novel synthesis of Prussian blue nanoparticles and nanocomposite sol: Electro-analytical application in hydrogen peroxide sensing - Pandey P.C.; Pandey A.K. (My University, 2025)
This paper reports a new method for the synthesis of Prussian blue nanoparticles (PBNPs) sol of homogeneous dispersion with average particle size to the order of 15.8 nm. The new method of PBNPs sol synthesis is based on the interaction of active concentrations of 3-aminopropylalkoxysilane, cyclohexanone and single precursor potassium ferricyanide under ambient conditions. The PBNPs sol shows excellent electrochemistry with electron transfer rate constant to the order of 32.1 s-1. The resulting PBNPs sol has been found highly stable for practical applications and shows functional activity for making nanocomposite sol with tris(2,2′-bipyridyl) ruthenium (Rubpy). The PB-Rubpy nanocomposite shows high sensitivity for H2O2 electrochemical sensing to the order of 1102.0 μA mM-1 cm -2 and storage stability of the materials for more than 3 months. In addition, these nanocomposite exhibits excellent electrocatalytic property for hydrogen peroxide (H2O2) sensing with catalytic rate constant to the order of 3.14 × 103 M-1 s -1. The PB-Rubpy nanocomposite sol, apart from electrocatalytic application, shows photoluminiscent ability for many opto-electroanalytical applications. In addition to that functional property of PBNPs sol for making nanodispersion with several known nanoparticles of gold, silver, palladium along with in situ synthesis of mixed metal hexacyanoferrate have also been observed. © 2012 Elsevier Ltd.